2016
DOI: 10.1016/j.nepig.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species analyses unravel the complexity of H3K27me3 and H4K20me3 in the context of neural stem progenitor cells

Abstract: Neural stem progenitor cells (NSPCs) in the human subventricular zone (SVZ) potentially contribute to life-long neurogenesis, yet subtypes of glioblastoma multiforme (GBM) contain NSPC signatures that highlight the importance of cell fate regulation. Among numerous regulatory mechanisms, the post-translational methylations onto histone tails are crucial regulator of cell fate. The work presented here focuses on the role of two repressive chromatin marks tri-methylations on histone H3 lysine 27 (H3K27me3) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…In addition, the repressive chromatin marks H3K27me3 and H4K20me3 were shown to play important roles in normal and disease conditions in the context of neural stem progenitor cells where H3K27me3 is found primarily at promoters in gene-rich regions, and is closely associated with developmental regulators in embryonic stem cells, including Hox and Sox genes. Moreover, their levels were altered in the human GBM [119]. In this context, our results indicated that the modified histones H3K4me, 3H3K9me, H3K27me, H3K27me3, and H4K20me3 were strongly reduced in the si-hVDAC1-TTs (Figure 4).…”
Section: Vdac1 Depletion Altered Histones Modifications Increasing Amentioning
confidence: 62%
“…In addition, the repressive chromatin marks H3K27me3 and H4K20me3 were shown to play important roles in normal and disease conditions in the context of neural stem progenitor cells where H3K27me3 is found primarily at promoters in gene-rich regions, and is closely associated with developmental regulators in embryonic stem cells, including Hox and Sox genes. Moreover, their levels were altered in the human GBM [119]. In this context, our results indicated that the modified histones H3K4me, 3H3K9me, H3K27me, H3K27me3, and H4K20me3 were strongly reduced in the si-hVDAC1-TTs (Figure 4).…”
Section: Vdac1 Depletion Altered Histones Modifications Increasing Amentioning
confidence: 62%
“…Additionally, we sought to interrogate the gene expression signature common across various GBM subclasses (http://tcgadata.nci.nih.gov/), 2,9 glioma stem cell profile, 14 and the SVZassociated GBMs. 10,16,17 Our analysis across these large data sets identified that 9 genes (PBK, CENPA, KIF15, DEPDC1, CDC6, DLG7, KIF18A, EZH2, HMMR) crucial for cell cycle, centromere assembly, and chromosome segregation were commonly upregulated that highlights a unique mechanism to distinguish GBM from non-neoplastic tissues. Further, the notion that region-specific neural stem and progenitor cells (NSPCs) may give rise to molecularly distinct subtypes of brain tumor upon dysregulation.…”
Section: Introductionmentioning
confidence: 92%
“…To ascertain characteristics of NSPCs as they exist in vivo for gene expression analysis, we purified NSPCs from the non-human primate baboon brain for deep RNA-Seq analysis to reveal gene expression pattern specific in NSPCs. 16,17 Using deep RNA-Seq, we had analyzed differential gene expression in MRI-classified group I and group II GBM compared with control specimens. Subsequently, we attempted the comparison of expression profiles between endogenous NSPCs and MRI-classified SVZ-associated GBM (Fig.…”
Section: Mri-classified Svz-associated Gbm Redirects Expression Signamentioning
confidence: 99%
See 2 more Smart Citations